2017
DOI: 10.4103/0973-6131.205516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selected yogic practices on pain and disability in patients with lumbar spondylitis

Abstract: Aim:The study was designed to find the effect of selected yogic practices on lumbar spondylitis.Materials and Methods:This was a prospective, randomized study without a control trial. A total of 172 participants with lumbar spondylitis (age 21–79 years) from the outpatient department (OPD) of neurosurgery, AIIMS, Bhubaneswar, were randomly assigned to receive yoga therapy. The module of selected yogic practices consisted of pawanamuktasana series 1 (loosening and strengthening), asana, pranayama, and relaxatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…have reported that yoga reduces the inflammatory markers [ 23 , 24 ]. These have been instrumental in translating benefits in persons who have arthritis, LBP, and neck pain [ 13 , 14 ]. The American Pain Society also brace yoga as an evidence-based treatment for LBP with at least moderate benefit [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…have reported that yoga reduces the inflammatory markers [ 23 , 24 ]. These have been instrumental in translating benefits in persons who have arthritis, LBP, and neck pain [ 13 , 14 ]. The American Pain Society also brace yoga as an evidence-based treatment for LBP with at least moderate benefit [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stretching causes the fullest elongation of muscle fiber and refines the muscle’s elasticity as well as reassert a rich tone, whereas isometric posturing can relieve muscle spasm and pain. There is overall increased muscle flexibility, control, improved ROM, and more significantly shifting to healthy habitual patterns of posture in daily life [ 13 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations